2016
DOI: 10.18404/ijemst.75656
|View full text |Cite
|
Sign up to set email alerts
|

A Policy-Relevant Instrumental Case Study of an Inclusive STEM-Focused High School: Manor New Tech High

Abstract: This instrumental case study of Manor New Tech High (MNTH) provides insight and understanding of a trend in U.S. education to create new STEM schools and increase the achievement of students underrepresented in STEM. MNTH was an inclusive, STEM-focused high school, in Manor, Texas. The creation of the school was stimulated by a statewide Texas STEM education policy initiative, seed money from private foundations, and local community support. MNTH was chosen for this study because of its diverse student populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
3
12
0
1
Order By: Relevance
“…The data showed that long-term lesson planning had significantly higher scores on the rubric as compared to the short-termed lessons. This difference is consistent with the literature regarding the need for students to have time to develop and practice skills (Lynch et al, 2017;NGSS Lead States, 2013). The extended time allows students to monitor and reflect on their progress while working toward self-regulation of the skill (Carpenter & Pease, 2013;English & Kitsantas, 2013).…”
Section: Short-term Vs Long-term Lessonssupporting
confidence: 91%
See 2 more Smart Citations
“…The data showed that long-term lesson planning had significantly higher scores on the rubric as compared to the short-termed lessons. This difference is consistent with the literature regarding the need for students to have time to develop and practice skills (Lynch et al, 2017;NGSS Lead States, 2013). The extended time allows students to monitor and reflect on their progress while working toward self-regulation of the skill (Carpenter & Pease, 2013;English & Kitsantas, 2013).…”
Section: Short-term Vs Long-term Lessonssupporting
confidence: 91%
“…Overall, there were no statistically significant differences in the total 21CLD scores across grade levels. This is consistent with the missions of the ISHSs in this study to shift responsibility for learning to the students by weaving 21 st Century skills throughout high school grade levels (Lynch et al, 2017). When looking at trends in long-term projects, there was a jump in total 21CLD score for 12th grade.…”
Section: Grade Level Differencessupporting
confidence: 85%
See 1 more Smart Citation
“…This article is derived from a larger study titled, Multiple Instrumental Case Study of Inclusive STEM-focused High Schools: Opportunity Structures for Preparation and Inspiration (Lynch et al, 2017). The purpose of this section was to describe the procedures for the larger study in order to validate and make transparent the data that was drawn for the engineering education study.…”
Section: Methodsmentioning
confidence: 99%
“…This case study acted as a validation step, authenticating the claim that the school only teaches through project based learning. Lynch et al (2017) described one project observed in a Geometry classroom where students were challenged to design a building provided specific parameters. Students worked in their groups to designate roles and expectations for their group work, based on a teacher-created rubric.…”
Section: Manor New Tech High School (Pbl)mentioning
confidence: 99%